Evolution and expression of LEAFY genes in ferns and lycophytes (2022)
Background: The LEAFY (LFY) transcription factors are present in algae and across land plants. The available expression and functional data of these genes in embryophytes suggest that LFY genes control a plethora of processes including the first zygotic cell division in bryophytes, shoot cell divisions of the gametophyte and sporophyte in ferns, cone differentiation in gymnosperms and floral meristem identity in flowering plants. However, their putative plesiomorphic role in plant reproductive transition in vascular plants remains untested. Results: We perform Maximum Likelihood (ML) phylogenetic analyses for the LFY gene lineage in embryophytes with expanded sampling in lycophytes and ferns. We recover the previously identified seed plant duplication that results in LEAFY and NEEDLY paralogs. In addition, we recover multiple species-specific duplications in ferns and lycophytes and large-scale duplications possibly correlated with the occurrence of whole genome duplication (WGD) events in Equisetales and Salviniales. To test putative roles in diverse ferns and lycophytes we perform LFY expression analyses in Adiantum raddianum, Equisetum giganteum and Selaginella moellendorffii. Our results show that LFY genes are active in vegetative and reproductive tissues, with higher expression in early fertile developmental stages and during sporangia differentiation. Conclusions: Our data point to previously unrecognized roles of LFY genes in sporangia differentiation in lycophytes and ferns and suggests that functions linked to reproductive structure development are not exclusive to seed plant LFY homologs.